Linking technology to business planning: theory and practice. (1st January 1999) - Probert, David; Farrukh, Clare; Gregory, Mike; Robinson, Nick
Over the last two decades there has been increasing practical interest in the integration of technology into the business planning process, while at the same time the output of research papers on this subject has grown apace. In this paper, we review the development of ideas in the field, drawing out common themes. The applicability and value of these themes has then been tested in practice, through the development of a technology review process with a collaborating company. The process is designed to incorporate technical and commercial knowledge from individuals across diverse business units in order that a corporate view of technology strategy may be formed. A five-process model for the management of technology is proposed to give a framework around which practical tools can be grouped coherently. The paper concludes by discussing the experience and learning, which have emerged from the case, and comments on aspects of technology strategy development, which are still not well supported by theory-based techniques.